Microglial Activation and Inflammation as a Factor in the Pathogenesis of Progressive Supranuclear Palsy (PSP) - Alster, Piotr; Madetko, Natalia; Koziorowski, Dariusz; Friedman, Andrzej (Frontiers in Neuroscience, 2020)
Progressive supranuclear palsy (PSP) is a neurodegenerative disease based on four-repeat tauopathy pathology. Currently, this entity is not fully recognized in the context of pathogenesis or clinical examination. This review evaluates the association between neuroinflammation and microglial activation with the induction of pathological cascades that result in tauopathy pathology and the clinical manifestation of PSP. Multidimensional analysis was performed by evaluating genetic, biochemical, and neuroimaging biomarkers to determine whether neurodegeneration as an effect of neuroinflammation or neuroinflammation is a consequence of neurodegeneration in PSP. To the best of our knowledge, this review is the first to investigate PSP in this context.